Unraveling the Impact of Covid-19: Financial Distress and Resilience in Indonesian Retail Giants - I Ketut Mangku; Andika Andika; Nadia; Melli Agustiani (Dinasti Publisher, 2023)
This study aims to analyze whether PT. Matahari Department Store Tbk, PT. Hero Supermarket Tbk, PT. MAP Active Adiperkasa Tbk, and PT. Erajaya Swasembada Tbk experienced financial distress during the 2019-2021 period. The sample of these four companies was selected using purposive sampling. Data analysis using the Altman Z-score method. It was found that two companies, PT. Hero Supermarket Tbk in 2019 and 2020, with Z-scores of 2.9510 and 2.5147, and PT. Matahari Department Store Tbk in 2020-2021 with Z-scores of 2.1954 and 2.6608 are in the gray area. Between the two companies, PT. Hero Supermarket Tbk is facing financial distress in 2021 with a Z-score of 0.9288. PT. MAP Active Adiperkasa Tbk and PT. Erajaya Swasembada Tbk, is in healthy financial condition, because their Z-score is greater than 2.88. In conclusion, this study is an important financial health analysis conducted for companies operating in the Supermarket & Convenience Store, Clothing & Textile Retail, and Electronic Retail industries. The Altman Z-score has proven to be a valuable tool in identifying the risk of financial distress